Electrochemical oxidation of mitoxantrone at a glassy carbon electrode - Brett, A. M. Oliveira (1999)
Mitoxantrone is an anthracycline used as an antitumour antibiotic for leukaemia and breast cancer treatment, due to its interaction with DNA. However, the molecular mechanism of the antitumour action is not completely understood. Using a glassy carbon electrode the electrochemical oxidation of mitoxantrone was shown to be a complex, pH-dependent, irreversible electrode process involving several metabolites. Comparison of the electrochemical oxidation behaviour of mitoxantrone, ametantrone and aminantrone enabled a deeper understanding of the mechanism and showed the relevance of electrochemical data for the understanding of the cytotoxicity of mitoxantrone. Since mitoxantrone and its oxidation products adsorb strongly on the electrode surface, causing severe problems of electrode fouling, reproducible electroanalytical determinations could only be done at very low concentrations and in an aqueous buffer supporting electrolyte containing 30% ethanol. The detection limit obtained was 10-7 M.